Cellular structured Cu2Sn0.8Co0.2S3 with enhanced thermoelectric performance realized by liquid-phase sintering. Issue 3 (4th January 2023) - Gu, Yan; Ai, Wen; Chen, Jiaxin; Zhao, Anqi; Hu, Xiaohui; Zong, Pengan; Pan, Lin; Lu, Chunhua; Wan, Chunlei; Wang, Yifeng
Abstract : Sn-assisted liquid phase sintering was adopted to form band barriers and dislocation arrays, making low-energy carriers and phonons scatter in the cellular structured Cu2 Sn0.8 Co0.2 S3, and a record-high ZT value of 1.03 at 773 K was obtained. Abstract : As an eco-friendly and earth-abundant thermoelectric material, P-type Cu2 SnS3 has been studied intensively, revealing a maximal ZT of ∼0.85 in Cu2 Sn0.8 Co0.2 S3 . Preliminarily in this work, increasing sintering temperature realized a high power factor of ∼14 μW cm −1 K −2 with a detrimental increase of electronic thermal conductivity and resulted in a lowered ZT of ∼0.6 at 773 K. Accordingly, a Sn-assisted liquid-phase sintering was adopted, obtaining a series of cellular structured Cu2 Sn0.8 Co0.2 S3 – x Sn ( x = 0–0.06) bulks with Cu2 Sn0.8 Co0.2 S3 grains mainly isolated by monoclinic-phase-rich boundaries with dense dislocation arrays, which functioned as barriers for both low-energy carriers and phonons at the same time. This caused a dramatic reduction of electrical conductivity and electronic thermal conductivity (maximally by 90% for both), with a simultaneous enhancement of Seebeck coefficient and a modest sacrifice of power factor, while more importantly, a strongly suppressed lattice thermal conductivity was observed. Finally, a maximum ZT of ∼1.03 at 773 K was achieved in the Cu2 Sn0.8 Co0.2 S3 –0.05Sn composite.